INDIKATOR SOSIAL – EKONOMI UNTUK PENGUKURAN KINERJA LINGKUNGAN KAWASAN INDUSTRI BERBASIS KELAPA SAWIT KEK SEI MANGKEI (IDENTIFICATION OF SOCIAL – ECONOMIC INDICATORS FOR ENVIRONMENTAL PERFORMANCE MEASUREMENT INDUSTRIAL AREAS BASED ON PALM OIL) - indah fajarwati (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2018)
SEZ Sei Mangkei is the realization of the MP3EI program, by developing the downstream palm oil industry in Indonesia. SEZ Sei Mangkei specialty is located in the center of raw materials and its strategic location to support SEZ Sei Mangkei development in the future. To be able to realize industrial sustainability, the company was asked to conduct an environmental performance assessment, by looking at various indicators. This study focuses on identifying social and economic indicators that affect environmental performance in the Sei Mangkei industrial area based on oil palm clusters. The research was conducted by survey method with data collection technique through interview and questionnaire. Data analysis is done quantitatively descriptive and qualitative. Based on the result of the research, it is concluded that identification of social and economic indicator variables in SEZ Sei Mangkei referring to Sustainability Reporting Guidelines (2011), based on GRI Reporting Framework (2010) can be implemented in SEZ Sei Mangkei, although there are some variables that have not been implemented properly, because there are still at least industries that operate in SEZ Sei Mangkei. Keywords: SEZ Sei Mangkei, oil palm, environmental performance, GRI 2010, social – economic indicators